Local electrochemistry and scanning probe microscopy techniques to clarify intergranular cracking phenomena in weldable martensitic stainless steels - Maier, J.; Kinsella, Brian; Bailey, Stuart; Becker, Thomas; Ladwein, T. (Omnipress, 2009)
Intergranular stress corrosion cracking (IGSCC) of weldable martensitic stainless steels (WMSS) has been a major concern in the oil and gas industry. It occurs under sweet and mildly sour wet service conditions and in the presence of hot chlorides. The cracking phenomenon is assumed to be due to the formation of chromiumrich carbides on former austenite grain boundaries in the heat affected zone of the weld. The chromium depletion in the surrounding matrix results in susceptibility to IGSCC. A combined approach using localized electrochemical measurements and scanning probe microscopy (SPM) techniques was utilized to locate sensitized zones in rich grade WMSS. The electrochemical measurements were performed using a custom built micro cell allowing measurements on small spot sizes. The resulting etched working electrode surfaces were then examined by atomic force microscopy (AFM). The electrochemical results corresponded well with local metal dissolution and etching imprints obtained using AFM respectively. Performing local electrochemical tests in combination with SPM investigation proved very valuable. The imprint on the working electrode surface left after electrochemical analysis revealed sensitized zones in both actual welded samples and simulated welded samples.